The new or electronic media, including social networking sites in particular, have brought about profound changes in the process of communication and social communication between people and human groups, and have contributed to changing many behaviors and - TEFERKNIT, Abdelkarim (Social Sciences Journal)
The new or electronic media, including social networking sites in particular, have brought about profound changes in the process of communication and social communication between people and human groups, and have contributed to changing many behaviors and behaviors, and have worked to bring about changes in the system of values, traditions and customs within Arab societies, which could not Its people resist what is swept away by the creeping current of globalization through social networking sites of a global, planetary nature, that is not restricted by borders, and is not governed by values or principles. Its bet is to spread, expand, and disseminate ideas and information of a temporary and consumer nature in most of them, ideas that may not be compatible and consistent with most of them. The Arab-Islamic societies, which were unable, in exchange for this, to stop this global wave, and did not provide an alternative to it through Arab social networking sites, which instead of activating the Arab-Islamic concerns and preoccupations, they are still lagging behind in carrying the aspirations of their societies and the principles and values of their people.